Formation of the first stars and black holes - Haemmerlé, Lionel; Mayer, L.; Klessen, Ralf S.; Hosokawa, T.; Madau, P.; Bromm, V. (Space science reviews, 2020)
We review the current status of knowledge concerning the early phases of star formation during cosmic dawn. This includes the first generations of stars forming in the lowest mass dark matter halos in which cooling and condensation of gas with primordial composition is possible at very high redshift (z>2